Legal Aid in Jināyāt and the Indonesian Criminal Code: An Account on Free Legal Advice - Sukiyawati; La Ode Bunga Ali; Rajasree; Zakurdaeva (Al-Ahkam: Jurnal Ilmu Syari’ah dan Hukum, 2023)
This study aims to investigate the comparison between the Law of Jināyāt Procedure and the The Code of Criminal Procedure (publicly known as KUHAP) in providing free legal aid for suspects. This research applies a normative juridical approach with legislative and conceptual perspectives, studying Qānūn Aceh Number 7 of 2013 on the law of Jināyāt Procedure and Law Number 8 of 1981 on the Code of Criminal Procedure. This article concludes that under The law of Jināyāt Procedure, an individual provided with legal advices is threatened with sixty lashes or a fine of one thousand and two hundred grams of pure gold or sixty months of imprisonment or more. Meanwhile, criminal procedural law limits the provision of legal advice to suspects facing imprisonment of five years or more, the death penalty, or fifteen years of imprisonment. This article suggests that the concept of free legal counsel provided by the state should be extended to all suspects.